Your name here - DeWitt, Helen, 1957-; Gridneff, Ilya (Deep Vellum/Dalkey Archive Press, 2025)
"A major literary event over two decades in the making, Your Name Here marks the seismic return of Helen DeWitt (The Last Samurai), and will introduce readers to the riveting voice of Ilya Gridneff. A book of unparalleled scope and vision, Your Name Here is a spectacular honeycomb of books-within-books. In this death-defying feat of ambition, collaborators Helen Dewitt and Ilya Gridneff weave together America's "War on Terror," countless years of literary history, authorial sleight of hand, Scientology, dream analysis, multiple languages, emails, images, graphs, into something wondrous and unique. A metafictional Pygmalion story reminiscent of Charlie Kaufman's Oscar-nominated Adaptation, or Italo Calvino's If on a winter's night a traveler; Your Name Here is a rare work of art that captures the process of becoming itself. A reminder that a masterpiece and a doomed voyage look the same at the start"-- Provided by publisher.